Psoriatic Juvenile Idiopathic Arthritis Associated with Uveitis: A Case Report - Davide Moretti; Ilaria Cianchi; Gaia Vannucci; Rolando Cimaz; Gabriele Simonini (Case Reports in Rheumatology)
According to the definition proposed by the International League of Associations for Rheumatology (ILAR), juvenile idiopathic arthritis (JIA) is defined as an arthritis of unknown etiology, starting under 16 years of age and lasting for at least 6 weeks, once other known conditions have been excluded. JIA represents the most common chronic rheumatic disease of childhood and is considered an important cause of short- and long-term acquired disability in children. It is currently estimated that psoriatic JIA represents up to 10% of all JIA subtypes, and chronic uveitis may occur in 10 to 15% of children with psoriatic JIA. In this report we describe a case of psoriatic JIA complicated by uveitis, in a child failing previous treatments with nonsteroidal anti-inflammatory drugs, methotrexate, and etanercept. Finally, adalimumab was prescribed, which led to sustained clinical remission in both arthritis and uveitis.